Childhood trauma and eating psychopathology: A mediating role for dissociation and emotion dysregulation?. (January 2015) - Moulton, Stuart J.; Newman, Emily; Power, Kevin; Swanson, Vivien; Day, Kenny
Abstract: The present study examined the relationship between different forms of childhood trauma and eating psychopathology using a multiple mediation model that included emotion dysregulation and dissociation as hypothesised mediators. 142 female undergraduate psychology students studying at two British Universities participated in this cross-sectional study. Participants completed measures of childhood trauma (emotional abuse, physical abuse, sexual abuse, emotional neglect and physical neglect), eating psychopathology, dissociation and emotion dysregulation. Multiple mediation analysis was conducted to investigate the study's proposed model. Results revealed that the multiple mediation model significantly predicted eating psychopathology. Additionally, both emotion dysregulation and dissociation were found to be significant mediators between childhood trauma and eating psychopathology. A specific indirect effect was observed between childhood emotional abuse and eating psychopathology through emotion dysregulation. Findings support previous research linking childhood trauma to eating psychopathology. They indicate that multiple forms of childhood trauma should be assessed for individuals with eating disorders. The possible maintaining role of emotion regulation processes should also be considered in the treatment of eating disorders.